Evaluating student satisfaction of terminological apparatus with natural and mathematical textbooks in Kazakhstani schools - Saniya Nurgaliyeva; Aziya Zhumabayeva; Tulebike Kulgildinova; Saltanat Abildina; Bakhtikhon Kurbonova; Akerke Umirbekova; Aidos Bolatov (Cogent Education)
This study evaluates student satisfaction with the terminological apparatus in natural and mathematical textbooks used in Kazakhstani schools. A quantitative cross-sectional design was employed, using a structured questionnaire administered to 678 students across various school types. Stratified random sampling ensured diversity in gender, residence, and study language. Key findings indicate that 84.7% of students found textbook terms clear, with males reporting significantly higher clarity than females (p < 0.001). Kazakh-speaking students reported slightly higher clarity than Russian-speaking counterparts, though this difference was not statistically significant. Most students relied on teachers to resolve unclear terms, making it the most effective strategy. Additional illustrations were useful for 81.1% of participants, especially in IT and natural sciences, though mathematics terminology remained challenging. These findings have educational policy implications, suggesting improvements in textbook terminology, teacher training, and curriculum design. Enhancing clarity through precise definitions, visual aids, and teacher support could improve student comprehension. Study limitations include reliance on self-reported data and the exclusion of qualitative insights from teachers and policymakers. Future research should integrate these perspectives for a more comprehensive understanding of textbook effectiveness.